Χρήση ενσιρωμένου ελαιοπλακούντα στα σιτηρέσια γαλακτοπαραγωγών αγελάδων - Κανάρης, Σάββας (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The scope of this research was to examine the effect of the silage olive cake (OC) on the dairy cow diet in terms of quantity and quality of the milk produced. The experiment used 24 cows of the HolsteinFriesian breed which allocated into two homogeneous groups of twelve animals according to their age, lactation period and their production and quality of milk. In the first group (group OC) included 5 kg of silage olive cake per cow per day, for a period of eight weeks, while in the control group (group CON) was given an isogenic and isoproteinic ration without the inclusion of olive cake. Milk sampling took place weekly with morning and afternoon milk mixing, while animal weight measurements, food consumption records, and blood sampling were performed throughout the experiment. The results of the experiment showed that the silage oil cake was completely consumed by the animals and had no effect on milk production throughout the experiment and milk yield ranged between 25.2 ± 7.19 L and 26.54 ± 7.21L for the OC group and CON, respectively. Moreover, the weight of the animals in the two groups was unaffected (average of: 561.67 Kg),neither the percentage of fat in milk which was 3.36 ± 0.30% and 3.21 ± 0.35% nor the percentage of protein which was 3.55 ± 0.12% and 3.52 ± 0.14% for the OC and CON groups, respectively Additionally, other components of milk like lactose and total solids remained unaffected. In conclusion, the results of the present study indicate that the use of olive cake on dairy cow diet can replace other feeds thus reducing feed costs without affecting the quantity or quality of the milk produced.
Keywords: Olive cake; Control group; Dairy production; Γαλακτοπαραγωγή